Enhancing the Modal Split in Paramaribo Through Design-Driven Participatory Action Research Fuelled by Urban Tactics - Sam Rymenants; Marlies Struyf; Sigrid Heirman; Marleen Goethals (Urban Planning, 2023)
There appears to be no “one-size-fits-all” strategy for evolving from a car-dependent urban environment towards a well-balanced modal split. The search for a suitable mobility strategy for a particular setting can be framed as seeking a suitable governance strategy. This article explores the opportunities of design-driven participatory action research (DD-PAR) as a governance strategy for improving mobility within a context of weak governance by investigating a single case study conducted in Paramaribo North, Suriname. Despite available plans, designs, and policy proposals, Surinamese public authorities are struggling to improve mobility. Notwithstanding many efforts, clientelism and patronage are weakening the power of the government, resulting in unimplemented public initiatives. Moreover, there are few civil society organisations to advocate for this weak public power. This creates a context in which neither the government nor civil society is sufficiently equipped to realise the modal shift in Paramaribo. Governance strategies depending on strong government or proactive civil society (e.g., actor-based strategies) are thus not suitable. In contrast, DD-PAR appears to have potential as a governance strategy, as it uses research and academics as forces to create societal enthusiasm, establish actor networks, and generate action. The current case study identifies key actors and preconditions for building a network of actors. It also provides tentative insights into urban tactics for increasing pressure on the government to provide adequate infrastructure and policy to accommodate newly developed action that supports a more diverse modal split.